The investigation of apoptosis-related genes in periodontitis - Sayad, Arezou; Hashemian, Fatemeh; Gholami, Leila; Jamali, Masoud; Badrlou, Elham; Sadeghpour, Saba; Nazer, Naghme; Khalilian, Sheyda; Ghafouri-Fard, Soudeh (BMC research notes, 2025)
This study aims at determination of the roles of five apoptosis-related genes, namely CASP2, CASP8, BCL2, HULC and PVT1 in the pathoetiology of periodontitis via measurement of their expressions in both peripheral blood and tissues of affected persons. CASP2 was over-expressed in gingiva of patients compared with healthy subjects (RME = 24.56, P < 0.001), and in both affected females and males (RME = 30.53, P = 0.03 and RME = 20.59, P = 0.01, respectively). BCL2 was higher in affected tissues compared with controls (RME = 32.28, P < 0.001) and in affected tissues of males versus controls (RME = 69.03, P < 0.001). Finally, HULC had lower level in the blood of patients (RME = 0.21, P = 0.01) and in the blood of female patients compared with normal females (RME = 0.15, P = 0.01). Other comparisons yielded no significant results. BCL2 and CASP2 had the highest diagnostic values for separation of diseased gingival tissues from normal ones. HULC has the best values in the distinction of blood samples of affected persons from control persons. Combination of transcript levels of CASP2, CASP8, BCL2, HULC and PVT1 changed AUC to 0.84 and 0.72 in tissues and blood samples, respectively. To conclude, these genes might be regarded as putative contributors in the pathophysiology of periodontitis.